Global and regional long‐term survival following resection for HCC in the recent decade: A meta‐analysis of 110 studies. Issue 7 (2nd March 2022) - Reveron‐Thornton, Rosyli F.; Teng, Margaret L. P.; Lee, Eunice Yewon; Tran, Andrew; Vajanaphanich, Sean; Tan, Eunice X.; Nerurkar, Sanjna N.; Ng, Rui Xin; Teh, Readon; Tripathy, Debi Prasad; Ito, Takanori; Tanaka, Taku; et al.
Abstract: Surgical resection for HCC remains a major curative treatment option, but it is unclear whether there are differences in outcomes by region and whether outcomes have improved over time. We aimed to estimate pooled overall survival (OS), recurrence‐free survival (RFS), and complication rates in patients with hepatocellular carcinoma (HCC) following curative surgical resection and to compare outcomes by region and by time period. In this systematic review and meta‐analysis, we searched Pubmed, Embase, and Cochrane databases from inception to May 15, 2020. We selected studies reporting OS, RFS, and complications in adult patients with HCC undergoing curative surgical resection. Two authors independently searched the literature and extracted the data. We screened 6983 articles and included 110 eligible studies with 82, 392 patients, with study periods spanning from 1980–2017. The global pooled 1‐year and 5‐year survival rates were 88.9% (95% confidence interval [CI] 87.1–90.4) and 56.2% (95% CI 52.8–59.6) for OS and 71.1% (95% CI 67.6–74.3) and 35.2% (95% CI 32.5–38.0) for RFS, respectively. Five‐year OS was higher in Asia (57.03%) than in other regions (Europe 48.3%; North America 48.0%; and South America 49.5%); p = 0.002. Five‐year RFS was higher in patients with hepatitis B virus versus patients with hepatitis C virus (34.8% vs. 24.1%; p = 0.02). There was no significant improvement in 5‐year OS and RFS over time. The pooled rate for complications was 27.6% (95% CI 23.4–32.3), with 9.7% (95% CI 6.3–14.7) classified as major. One‐year OS after surgical resection for HCC is excellent ( 90%). However, 5‐year OS ( 55%) and RFS ( 35%) are still poor, suggesting that long‐term care is suboptimal. Greater efforts are required to improve survival through enhanced surveillance and preventing recurrence through antiviral therapy. Abstract : In this meta‐analysis of 110 studies and 82, 392 patients, 1‐year and 5‐year overall survival were 89% and 56%, and recurrence‐free survival 71% and 35%, with no significant changes between studies before 2010 and those from 2010 and later. By region, the 5‐year overall survival was significantly higher in Asia compared with other regions. Although early surgical outcomes are excellent for HCC, long‐term overall and recurrence‐free survival remain poor, therefore greater adherence to antiviral therapy and surveillance is required after resection.image